Challenges of developing, conducting, analysing and reporting a COVID-19 study as the COVID-19 pandemic unfolds: an online co-autoethnographic study - Rachael Hunter (BMJ Open, 2021)
Objectives: To capture the complexities and unique experience of a newly formed multidisciplinary and multicentre research team developing and deploying a COVID-19 study and to identify lessons learnt.Design: Co-autoethnographic study.Setting: Staff at two UK academic institutions, a national charity and two major UK hospitals.Participants Researchers, clinicians, academics, statisticians and analysts, patient and public involvement representatives and national charity.Method: s The sampling frame was any content discussed or shared between research team members (emails, meeting minutes, etc), standard observational dimensions and reflective interviews with team members. Data were thematically analysed.Results: Data from 34 meetings and >50 emails between 17 March and 5 August 2020 were analysed. The analysis yielded seven themes with ‘Managing our stress’ as an overarching theme.Conclusion: Mutual respect, flexibility and genuine belief that team members are doing the best they can under the circumstances are essential for completing a time-consuming study, requiring a rapid response during a pandemic. Acknowledging and managing stress and a shared purpose can moderate many barriers, such as the lack of face-to-face interactions, leading to effective team working.